Interpersonal Communication Using Personal Sport Device In Forming Community - Adriani, Vanny; Chrisdina; Irwandy, Deddy (Journal of Communication and Public Relations, 2024)
Technologies matched the effectiveness of various health activity strategies, such as exercise monitoring, information, and social support. The purpose is to find out that technology has become part of delivering sports information that is used by the applications and devices, creating communication between individuals and devices they used to plan and record sports and exercise routines, physical performance, and record all the activity. Effective communication can occur if the sender and the recipient have good skills in exchanging messages. This study may provide an overview of verbal and nonverbal that may occur during communication in sports activities. This manuscript analyze whether technology enhances or hinders Interpersonal Communication using George Herbert Mead's Symbolic Interaction Theory. It uses a technique that includes a literature review and interviews with certain users of personal sports equipment to examine three fundamental concepts: mind, self, and society. According to the study, a person's capacity to interpret symbols is what makes up their mind. Therefore, everyone must interact to develop their mind and get that meaning. Then, the self is the ability to accept and adapt based on the judgment of another person's point of view. Moreover, an individual in the surrounding environment will deliver people in the process of taking tasks in society; they even can form a community as the same user of personal sports devices. Using Symbolic Interaction Theory, humans will perform an action based on the meanings attached to the action. Nevertheless, humans can obtain their purpose from social interaction with others.